Exploring the impact of knowledge, socialisation, and enjoyment on youth's motivation to visit the Borneo Cultures Museum, Sarawak / Izwana Md. Ideris @ Idris ... [et al.] - Md. Ideris@Idris, Izwana; Mohamad Yusof, Nur Fakiera; Zainuddin, Nur Sahirah; Gatu, Alvin; Mohamad Musa, Nurafiqah; Mohd Zaidi, Nur Murniza (Universiti Teknologi MARA, Perak, 2025)
The museum has been one of the most visited attractions in every country. Researchers have conducted extensive research on museums, yet they haven't specifically focused on the factors that influence young youths’ motivation to visit them. Hence, the purpose of this study was to examine the factors affecting youths’ motivation to visit museums. The study used a quantitative approach, and the youths from Sarawak served as the unit of analysis. Through non-probability sampling and applied purposive sampling, 388 data samples were collected via an online survey and a face-to-face survey, whereby they were collected from a specific target group between the ages of 18 and 30 in Sarawak. The survey instrument was adopted from previous studies with minor modifications, validated, and pilot tested. A total of 388 usable samples were analysed using descriptive and multiple regression analyses. The result indicated that three predictors (knowledge, enjoyment, and socialisation) significantly affect youth when visiting museums. This study adds to the existing literature on museums and has practical implications for the museum as a whole.